Hageman Factor C46T Promoter Gene Polymorphism in Patients with Hypercortisolism - Świątkowska-Stodulska, R.; Kitowska, A.; Skibowska-Bielińska, A.; Wiśniewski, P.; Sworczak, K. (Hormone and Metabolic Research, 2014)
Glucocorticoids are a group of hormones with a particularly significant effect on hemostasis. In hypercortisolemic patients increased concentrations of II, VIII, and von Willebrand factors were reported. Considerably fewer studies were concerned with factor XII (FXII). There are reports of decreased FXII concentrations in both venous and arterial thrombosis patients. Also, it was determined that FXII C46T promoter gene polymorphism leads to changes of its concentration. The aim of the study was to determine the C46T polymorphism of FXII promoter gene in hypercortisolemic patients. Thirty hypercortisolemic patients were enrolled in the study. Twenty-nine healthy individuals served as controls. Genomic DNA was isolated from peripheral blood leukocytes. To analyse the polymorphism, PCR products were digested by Hga I at 37°C for 23 h, subjected to 2% agarose gel, and stained with ethidium bromide. In all subjects FXII activity was determined using a clot-based method. All statistical calculations were performed using STATA 12.0 software. A p-value lower than 0.05 was considered statistically significant. Prevalence of FXII C46T polymorphism did not differ significantly between hypercortisolemic patients and controls. No correlation was found between FXII activity and its gene promoter polymorphism in the hypercortisolemic group; however, a clear trend was recorded toward higher FXII activities in 46C homozygotes, and lower in 46T homozygotes. Mean FXII activities did not differ significantly between hypercortisolemic patients and the control group. It seems that in hypercortisolemic patients no significant disorders are present concerning FXII concentrations due to the C46T polymorphism of its gene promoter.
Keywords: coagulation factor XII; Cushing’s syndrome; subclinical Cushing’s syndrome